Diplomatie und ihre Einflüsse - Nina Hechenblaikner (Österreichische Zeitschrift für Geschichtswissenschaften)
The Vienna follow-up meeting achieved an unprecedented breakthrough for the human dimension of the CSCE. This article explores this success by analysing three different levels: governments, delegations, and non-governmental players. Each government and its relationship with other nations formed the basis for the positions taken by its delegation. Nonetheless, the outcome of the meeting depended heavily on the negotiation skills of the diplomats. Hence, the delegates were at the centre of the negotiation process and were crucial to the understanding of the success of the meeting. External factors, in particular human rights organizations, although not allowed to take part in the negotiations, contributed to the process. This article argues that only by taking all three into consideration can the success be fully understood.